Comparison of curriculum strategies for the prevention of child sexual abuse (CSA) in developing and developed countries - Misselina Madya Gerda (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research is an integrative literature review regarding comparison of curriculum policies in preventing Child Sexual Abuse (CSA) in Developing and Developed Countries. This research focuses on the Child Sexual Abuse (CSA) prevention curriculum. Data collection was obtained from four different databases: Science Direct, SCOPUS, ERIC (Ebscohost) using six different search terms. A total of 77 publications were found. Based on school safety 2, child sexual abuse 19, school-based prevention 29, CSA prevention education 27 publications were included in the data analysis. The findings from this literature study are intended to provide new information to stakeholders in schools regarding the analysis of differences in the implementation of preventive policies by developed and developing countries. The literature study indicates that developed countries are more effective in implementing curriculum policies to prevent sexual violence against early childhood than developing countries, highlighting the influence of resource disparities.